2018
DOI: 10.1039/c8nj02713g
|View full text |Cite
|
Sign up to set email alerts
|

Quinoxaline as an integrated directing group in palladium-catalyzed ortho-C–H bond arylation of the aryl unit of 2-arylquinoxalines

Abstract: ortho-Directed arylation of the C(sp2)–H bond of 2-arylquinoxalines with a broad range of aryl bromides was achieved using phosphine-free Pd(OAc)2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…We began our investigations by evaluating the reactivity of a palladium catalyst for the C−H bond arylation of 2,3‐diphenylpyrazine (Scheme 1, top). Using our previous conditions for the C−H bond arylation of 2,3‐diphenylquinoxaline, [8] (namely Pd(OAc) 2 as catalyst associated with KOAc as the base in DMA at 150 °C with 1.5 equivalents of 2,3‐diphenylpyrazine) we were pleased to find that only mono‐arylation of one of the two phenyl rings occurred, although the desired arylated product 1 was isolated in a very poor 28 % yield due to the formation of Ullmann‐type aryl bromide homocoupling as the main side‐product [10] . Tetraalkylammonium salts have been highly successful in enhancing the reactivity and selectivity in Pd‐catalyzed cross‐coupling reactions, [11] including in C−H bond arylations [12] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We began our investigations by evaluating the reactivity of a palladium catalyst for the C−H bond arylation of 2,3‐diphenylpyrazine (Scheme 1, top). Using our previous conditions for the C−H bond arylation of 2,3‐diphenylquinoxaline, [8] (namely Pd(OAc) 2 as catalyst associated with KOAc as the base in DMA at 150 °C with 1.5 equivalents of 2,3‐diphenylpyrazine) we were pleased to find that only mono‐arylation of one of the two phenyl rings occurred, although the desired arylated product 1 was isolated in a very poor 28 % yield due to the formation of Ullmann‐type aryl bromide homocoupling as the main side‐product [10] . Tetraalkylammonium salts have been highly successful in enhancing the reactivity and selectivity in Pd‐catalyzed cross‐coupling reactions, [11] including in C−H bond arylations [12] .…”
Section: Resultsmentioning
confidence: 99%
“…13 C NMR (101 MHz, CDCl 3 ) δ 154. 8,152.5,142.3,141.0,140.7,139.8,138.3,135.9,130.8,130.6,130.2,129.8,128.5,127.5,127.5,125.1,22.3,20.4. MS (EI,70 eV) 4,152.4,151.1,146.9,143.0,141.6,138.0,137.5,135.8,133.6,130.6,130.3,129.8,129.6,129.3,128.7,128.0,127.6,127.1,22.2.…”
Section: -Methyl-3-(3'-(trifluoromethyl)-[11'-biphenyl]-2-yl)pyrazimentioning
confidence: 99%
See 2 more Smart Citations
“…A bidentate pyrazine-2-carboxamide group efficiently directed Pd(II)-catalyzed acetoxylation of remote ε-C(sp 2 )-H bonds in 3-phenylthiophene substrates [67]. To the best of our knowledge, there is no example of direct arylation of ortho-C-H bonds of 2,3-diphenylpyrazines under Ru(II)-catalyzed conditions, whereas Doucet and co-workers have shown that fused analogs, 2,3-diphenylquinoxalines underwent Pd-catalyzed ortho-C-H bond functionalization leading to monoarylated products, while the arylation reaction did not occur in the presence of [RuCl 2 (p-cymene)] 2 as a catalyst [68].…”
Section: Introductionmentioning
confidence: 99%